Ayurveda In Oncology: Symptomatic Relief In Recurrent Breast Cancer Lesion - Manish, Acharya; Chaudhary, Gitika; Richa; Biswas, Priyanka; Anushma (International Research Journal of Ayurveda & Yoga, 2026)
Breast cancer remains the most commonly diagnosed cancer globally, with rising incidence and recurrence rates, particularly in postmenopausal women. In India, projections estimate over 200,000 new cases annually by 2030. Despite advancements in conventional oncology, the recurrence of breast cancer lesions, especially years after initial treatment, continues to challenge long-term survivorship. This case study highlights the integrative potential of Ayurvedic treatment in managing recurrent breast cancer lesions. A 52-year-old female with a history of breast carcinoma presented to Jeena Sikho Lifecare Limited Hospital, Lucknow, Uttar Pradesh, India, with a cauliflower shaped proliferative reddish mass on the left breast, accompanied by white discharge and localized pain. She was undergoing oral chemotherapy and antihypertensive treatment. Ayurvedic inpatient management included therapies such as Snehana, Swedana, Matra Basti, Shirodhara, Jalaukavacharana (leech therapy), Pichu, Rasayana formulations, and personalized lifestyle and dietary modifications. Following treatment, the patient experienced marked symptomatic relief, with resolution of discharge and pain, no emergence of new complaints, and improved overall health. This case underscores the value of Ayurveda as a holistic alternative or complementary therapy for breast cancer recurrence and emphasizes the need for further clinical validation through controlled studies to establish standardized, evidence-based integrative cancer care protocols.